The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2mh01140a
|View full text |Cite
|
Sign up to set email alerts
|

Thermally conductive and compliant polyurethane elastomer composites by constructing a tri-branched polymer network

Abstract: This work synthesizes three kinds of polyurethane elastomers to verify the relationship between macroscopic and viscoelastic properties with the given branched factor of work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…4h presents statistical data representing the relationship between the thermal conductivity and elastic modulus of silicone, foams, ceramics, and various polymeric composites enhanced with fillers such as LM, carbon nanotubes, and graphene, among others. 15,19,27,34,37,45,50,[59][60][61][62][63] The composite material thus developed, featuring low modulus, high deformability, and high k, demonstrates pressure-controlled heat dissipation capabilities and dynamic thermal dissipation in complex environments. This surpasses the heat dissipation performance of commercial TIMs, highlighting its potential as a high-performance TIMs for flexible electronics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4h presents statistical data representing the relationship between the thermal conductivity and elastic modulus of silicone, foams, ceramics, and various polymeric composites enhanced with fillers such as LM, carbon nanotubes, and graphene, among others. 15,19,27,34,37,45,50,[59][60][61][62][63] The composite material thus developed, featuring low modulus, high deformability, and high k, demonstrates pressure-controlled heat dissipation capabilities and dynamic thermal dissipation in complex environments. This surpasses the heat dissipation performance of commercial TIMs, highlighting its potential as a high-performance TIMs for flexible electronics.…”
Section: Resultsmentioning
confidence: 99%
“…19,25,26 By controlling these aspects, it becomes possible to lower the modulus of polymer-based TIMs, which is beneficial for reducing contact thermal resistance. In this regard, Shi et al 27 reported thermally conductive and compliant polyurethane elastomer/Al composites by constructing a tri-branched polymer network, exhibiting a thermal conductivity (k) of around 1.8 W m À1 K À1 , a low Young's modulus of 640 kPa, and a low thermal contact resistance (R c ) of 0.11 K cm 2 W À1 . Besides, trapped entanglements imposed a preordained lower limit on the elastic modulus, with G 4 G e D rRT/M e , where G e represents the modulus due to entanglements, and M e is the number-average molar mass of the entanglement strand.…”
Section: Introductionmentioning
confidence: 99%
“…The uninterrupted 3D structure can provide minimal interfacial thermal resistance, guaranteeing that the majority of the heat is conducted through the filler network, which enhances the thermal conductivity of composite materials that are based on polymers. [29][30][31][32][33] Li et al successfully generated a pioneering 3D network of SiC skeleton with a SiO 2 core-shell structure. 34 Compared to traditional composite materials, composite materials based on 3D filling networks exhibit significantly improved thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al [ 38 ] synthesized polyurethane resins with functional side chains, which allow for specific functional modifications of the polyurethane. Shi et al [ 39 ] prepared a series of polyurethanes with tunable properties by grafting common inexpensive side chains. Nonetheless, few people have optimized the mechanical properties of polyurethane by side chains and further used them in 3D printing to fabricate stretchable sensors.…”
Section: Introductionmentioning
confidence: 99%